Neighborhood effect and obesity in adult survivors of pediatric cancer: A report from the St. Jude lifetime cohort study. Issue 2 (6th November 2019) - Howell, Carrie R.; Wilson, Carmen L.; Yasui, Yutaka; Srivastava, Deo K.; Lu, Wei; Bjornard, Kari L.; Ehrhardt, Matthew J.; Brinkman, Tara M.; Chemaitilly, Wassim; Hodges, Jason R.; Lanctot, Jennifer Q.; Robison, Leslie L.; et al.
Abstract : Survivors of childhood cancer are at risk for obesity, a condition potentially modifiable if dietary intake and physical activity are optimized. These health behaviors are likely influenced by neighborhood of residence, a determinant of access to healthy, affordable food and safe and easy exercise opportunities. We examined associations between neighborhood level factors and obesity among survivors in the St. Jude Lifetime cohort and community comparison group members. Persons with residential addresses available for geocoding were eligible for analysis ( n = 2, 265, mean age 32.5 [SD 9.1] years, 46% female, 85% white). Survivors completed questionnaires regarding individual behaviors; percent body fat was assessed via dual X‐ray absorptiometry (obesity: ≥25% males; ≥35% females); neighborhood effect was characterized using census tract of residence (e.g., neighborhood socioeconomic status [SES], rurality). Structural equation modeling was used to determine associations between neighborhood effect, physical activity, diet, smoking, treatment exposures and obesity. Obese survivors ( n = 1, 420, 62.7%) were more likely to live in neighborhoods with lower SES (RR: 1.23, 95% CI: 1.10–1.38) and rural areas (RR: 1.22, 95% CI: 1.07–1.39) compared to survivors with normal percent body fat. Resource‐poor neighborhoods (standardized effect: 0.06, p < 0.001) and cranial radiation (0.16, p < 0.001) had direct effects on percent body fat. Associations between neighborhood of residence and percent body fat were increased (0.01, p = 0.04) among individuals with a poor diet. Neighborhoods where survivors reside as an adult is associated with obesity. Interventions targeting survivors should incorporate strategies that address environmental influences on obesity. Abstract : What's new? The neighborhood where a childhood cancer survivor resides likely influences obesity risk and obesity‐related health behaviors. Little is known, however, about the impact of the so‐called neighborhood effect, which is driven by factors such as socioeconomic status (SES), access to healthy foods, and exercise opportunities, on obesity risk among survivors of childhood cancer. Here, investigation of survivors in the St. Jude Lifetime cohort shows that obesity risk is significantly increased in particular among survivors living in rural areas or in neighborhoods with relatively low SES. Obesity risk was further linked to age, exposure to cranial radiation, and inadequate physical activity.